Antimicrobial bacterial cellulose nanocomposites prepared by in situ polymerization of 2-aminoethyl methacrylate - Figueiredo, Ana R. P.
Antimicrobial bacterial cellulose/poly(2-aminoethyl methacrylate) (BC/PAEM) nanocomposites were prepared by in situ radical polymerization of 2-aminoethyl methacrylate, using variable amounts of N,N-methylenebis(acrylamide) (MBA) as cross-linker. The obtained nanocomposites were characterized in terms of their structure, morphology, thermal stability, mechanical properties and antibacterial activity. The ensuing composite membranes were significantly more transparent than those of pure BC and showed improved thermal and mechanical properties. The antibacterial activity of the obtained nanocomposites was assessed towards a recombinant bioluminescent Escherichia coli and only the non-crosslinked nanocomposite (BC/PAEM) proved to have antibacterial activity. (C) 2015 Elsevier Ltd. All rights reserved.